The Influence of Casting Methods on Microstructure of Al-Mg-Sc-Zr Alloy - Slapakova, Michaela; Krivska, Barbora; Grydin, Olexandr; Cieslar, Miroslav (Manufacturing Technology Journal, 2018)
Two methods of fabrication of Al-Mg-Sc alloy are compared - conventional casting followed by cold-rolling and twin-roll casting. To the advantages of twin-roll casting belong the lower material and energy requirements during the production. However, twin-roll cast material exhibits different initial microstructure and routes established for conventionally cast materials cannot be applied. In twin-roll cast material the distribution of primary particles is more inhomogeneous - they form segregation near the center and edges of the sheet and their average size is smaller. On the contrary, the average sub-grain size is much higher in the twin-roll cast material.
Keywords: Al-Mg; Twin-roll casting; Conventional casting; Central segregation; Particles distribution